BbMP-1, a new metalloproteinase isolated from Bothrops brazili snake venom with in vitro antiplasmodial properties. (November 2015) - Kayano, Anderson M.; Simões-Silva, Rodrigo; Medeiros, Patrícia S.M.; Maltarollo, Vinícius G.; Honorio, Kathia M.; Oliveira, Eliandre; Albericio, Fernando; da Silva, Saulo L.; Aguiar, Anna Caroline C.; Krettli, Antoniana U.; Fernandes, Carla F.C.; Zuliani, Juliana P.; et al.
Abstract: This study describes the biochemical and functional characterization of a new metalloproteinase named BbMP-1, isolated from Bothrops brazili venom. BbMP-1 was homogeneous on SDS-PAGE, presented molecular mass of 22, 933Da and pI 6.4. The primary structure was partially elucidated with high identity with others metalloproteinases from Viperidae venoms. The enzymatic activity on azocasein was evaluated in different experimental conditions (pH, temperature). A significant reduction in enzyme activity after exposure to chelators of divalent cations (EDTA), reducing agents (DTT), pH less than 5.0 or temperatures higher than 45 °C was observed. BbMP-1 showed activity on fibrinogen degrading Aα chain quickly and to a lesser extent the Bβ chain. Also demostrated to be weakly hemorrhagic, presenting however, significant myotoxic and edematogenic activity. The in vitro activity of BbMP-1 against Plasmodium falciparum showed an IC50 of 3.2 ± 2.0 μg/mL. This study may help to understand the pathophysiological effects induced by this group of toxin and their participation in the symptoms observed in cases of snake envenomation. Moreover, this result is representative for this group of proteins and shows the biotechnological potential of BbMP-1 by the demonstration of its antiplasmodial activity. Graphical abstract: Highlights: Biochemical and functional characterization of a new metalloproteinase. BbMP-1 isolated from Bothrops brazili snake venom. The in vitro activity of BbMP-1 against Plasmodium falciparum.